Illness and Metaphor - Cardona Suárez, Luis Fernando (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
In the present text we approach the question of our experience of illness and pain in the light of philosophical anthropology. As beings endowed with words, this experience is always mediated by our way of speaking about it. The power to name what happens to us configures us as peculiar organic individuals, compared to other forms of life. But when talking about our pains and illnesses we fall into a profound paradox: we have the need to communicate our pain to others, which is something so intimate and private that it individualizes; on the other hand, the understanding of the others of our experience finds, however, an almost insurmountable limit. Often, this limit is usually bordered by metaphor and its translative language. We want to examine, next, the relationship that we can establish between illness, pain and metaphor.